2021
DOI: 10.3390/ijms222312774
|View full text |Cite
|
Sign up to set email alerts
|

Development of Minicircle Vectors Encoding COL7A1 Gene with Human Promoters for Non-Viral Gene Therapy for Recessive Dystrophic Epidermolysis Bullosa

Abstract: Recessive dystrophic epidermolysis bullosa (RDEB) is a rare autosomal inherited skin disorder caused by mutations in the COL7A1 gene that encodes type VII collagen (C7). The development of an efficient gene replacement strategy for RDEB is mainly hindered by the lack of vectors able to encapsulate and transfect the large cDNA size of this gene. To address this problem, our group has opted to use polymeric-based non-viral delivery systems and minicircle DNA. With this approach, safety is improved by avoiding th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Recessive dystrophic epidermolysis bullosa (RDEB) is one of the most severe subtypes of the rare debilitating skin disorder, which is caused by mutations in COL7A1 gene leading to absent, malformed or deficient type VII collagen (C7) and thus anchoring fibrils. , This results in the separation of the epidermis from the dermis following minimal trauma or friction. , Exon excision strategy has been developed as a promising approach to treat RDEB. For instance, exon 80 or exon 73, that are exons with high prevalence of mutations for the disease, have been successfully excised by the usage of CRISPR, achieving restoration of collagen VII levels .…”
Section: Resultsmentioning
confidence: 99%
“…Recessive dystrophic epidermolysis bullosa (RDEB) is one of the most severe subtypes of the rare debilitating skin disorder, which is caused by mutations in COL7A1 gene leading to absent, malformed or deficient type VII collagen (C7) and thus anchoring fibrils. , This results in the separation of the epidermis from the dermis following minimal trauma or friction. , Exon excision strategy has been developed as a promising approach to treat RDEB. For instance, exon 80 or exon 73, that are exons with high prevalence of mutations for the disease, have been successfully excised by the usage of CRISPR, achieving restoration of collagen VII levels .…”
Section: Resultsmentioning
confidence: 99%
“…The transfection of embryonic stem-cell-derived neural stem cells (NSC) with a minicircle did not affect cell division kinetics, morphology or differentiation potential to astrocyte and neurons [ 50 ]. For a non-viral topical treatment of patients with Recessive Dystrophic Epidermolysis Bullosa (RDEB), a severe genetic skin disorder caused by mutations in the COL7A1 gene, RDEB skin cells were transfected with a minicircle expressing the large cDNA size of the COL7A1 gene (8.9-kb) to restore the expression and secretion of the structural protein-type-VII collagen (C7) at the dermal and epidermal junction [ 51 ]. The transfection of mesenchymal stem cells (MSCs) using a minicircle expressing the human angiopoietin 1 (ANGPT1) enhanced the MSC therapy by mediating a reduced pulmonary inflammation and lung permeability in lipopolysaccharide-induced acute lung injury (ALI) in mice [ 52 ].…”
Section: Non-viral Expression Vectors Totally Devoid Of Sequences Of ...mentioning
confidence: 99%
“…Most approaches under study for EB therefore focus on topical treatment [ 109 ], either by topical compound delivery (e.g., in vivo gene-addition by viral [ 110 ] or minicircle non-viral vectors [ 111 ], antisense oligonucleotides [ 112 ]), ex vivo gene-replacement or gene-correction followed by injection of corrected fibroblasts [ 113 ], or the transplantation of large epidermal sheets cultured from ex vivo -corrected keratinocytes [ 114 , 115 , 116 , 117 ], analogous to the treatment of full-thickness burn-wounds [ 118 ]. In 2017, Hirsch et al reported a 7-year-old boy with laminin 332-deficient JEB in whom almost the entire epidermis (~0.85 m 2 ) was replaced using exogenously corrected, autologous skin grafts [ 119 , 120 ].…”
Section: Revertant Mosaicism As Treatment For Genodermatosesmentioning
confidence: 99%